The Other Criticism in the Comparison Book of Alamdee 370AH - Haider Ismail Askar, Dr. (lark, 2022)
The presence of the critical (ego) and its attempt to appear must necessitate the other critical (the analogous and similar) and put his perceptions and ideas of interest. The awareness requires him to build a communicative dialogue thought. This will achieve the intention that was developed in the concepts of the self and the other and their effectiveness in producing the budget book. So, the other critical has an active presence in founding, discussing, and the findings that the book shows. Thus, the construction of the monetary balancing is not established in a vacuum, but rather from previous ideas represented by the other monetary. This necessitated its continuous presence in the monetary blog (Comparison). The presence of the other monetary illuminates monetary issues and contributes directly and indirectly to the formation of monetary awareness of the author (the ego) as an exciter based.  That is the exciter results in forecast-horizon that break it to produce the production of the critical discourse. Therefore, the communication between the self (Al-Amidi) and the (critical other) present occurs strongly in his critical blog (Comparison)
Keywords: the other, criticism, balance ,Alamdee, memory